ALPHABET BOX AS A MEDIA FOR LETTER PRONOUNCIATION TO INTRODUCE ENGLISH FOR PRIMARY SCHOOL - Fitrah Yuliawati; Iis Faida (PROJECT (Professional Journal of English Education), 2024)
The aim of this research is to recognize letters by using alphabet box media in a good pronounciation for primary students. This research uses qualitative research. From the results of the analysis stage, in the learning process students cannot differentiate between letters that have almost the same shape, for example "b" and "d", "p" and "q". This is because students do not memorize the letters of the alphabet and the learning media used by teachers is less interesting. Based on the analysis stage, so researchers uses media in the form of an alphabet box to improve the letter recognition skills of class 1 elementary school students in recognizing letters. Data collection techniques use observation, interviews, questionnaires and documentation. The results of collaborative assessment between researchers and teacher at SDN Batokarang 1 showed very good results, this shows that the alphabet box learning media is suitable to be used in the letter pronounciation skills of class1 students at SDN Batokarang 1.